Enzymatically hydrolyzed diet improves growth performance and intestinal microbiome in growing pigs - Gong, Tianye; Ji, Mengting; Yang, Yuting; Liu, Jingchao; Gong, Yuxuan; Liu, Sijun; Zhao, Yan; Cao, Guoqing; Guo, Xiaohong; Yang, Yang; Li, Bugao (Frontiers in Nutrition, 2024)
BackgroundThe use of enzymes within pig feed can reduce the challenges associated with antibiotic-free animal feeding. However, this enzymatic effect is often limited by the internal and external gut environment. This study aimed to improve diet quality and assess the impact of an enzymatically hydrolyzed diet (EHD) on growth performance, meat quality, and intestinal health in growing pigs.MethodsThe EHD was prepared by treating a liquid basal diet with a compound enzyme preparation (5 non-starch polysaccharides (NSP) enzymes: cellulase, pectinase, xylanase, β- glucanase, α-galactosidase; 3 exogenous digestive enzymes: amylase, lipase, protease; lysozyme, and glucose oxidase) in a 1:2.5 ratio with water and heated at 40°C for 1 h. Thirty-six growing pigs (average body weight 25 ± 0.5 kg; age 75 ± 3 days) from the Duroc × Landrace × Yorkshire crossbreed were randomly divided into three dietary groups: solid basal diet (S-CON), liquid basal diet (L-CON), and EHD.ResultsEnzymatic pre-treatment reduced the anti-nutritional factors (ANFs) in the diets (p < 0.01). Additionally, the gluconic acid in the EHD might reduce the pH of diets and inhibit pathogenic bacteria growth. Pigs fed the EHD had higher average daily gains (p < 0.01) and lower feed-to-gain ratios (p < 0.01). Muscle samples revealed higher meat redness and reductions in drip loss, shear force, cooking loss, and meat yellowness (p < 0.01). Moreover, the EHD increased intestinal concentrations of amylase and cellulase (p < 0.01). In terms of gut health, pigs on the EHD diet presented more aligned small intestinal villi, with improved villus height and villus crypt ratio (p < 0.01). There was also up-regulation of the abundance of the tight junction proteins Occludin and ZO-1 and down-regulation of the mRNA expression of TNF-α and IL-6 in the colon (p < 0.05). Additionally, the abundance of beneficial intestinal flora, particularly Firmicutes and Lactobacillus, increased significantly. Lactobacillus and Prevotella were positively correlated with increased short-chain fatty acids.ConclusionOverall, the EHD substantially improved growth performance and intestinal health in pigs, providing a potential reference for improving the effectiveness of enzymatic pretreatment in animal diets.